Development of Archimedes Law Material E-Module on Motion Systems to Improve Student's Concept Understanding - Yanarti Yanarti; Jumadi Jumadi; Ira Lelita; Wiwin Rosiningtias (Jurnal Penelitian Pendidikan IPA, 2022)
The development research carried out intends to develop an Archimedes Law Material E-Module on the Motion System to improve the understanding of the Learner's Concept. Product development uses the ADDIE model. Validation of material experts, media experts and testing the responses of teachers and students is a product trial design carried out. The validation of the material and the E-module media was carried out by five peer reviewers, the teacher response questionnaire was carried out by four teachers from several schools in Yogyakarta and Central Java. The E-Modul trial was tested on 25 class VIII students of SMPIT Bakti Insani with a quasi-experimental pretest posttest control group design. The results of the material expert validation data showed an average of 96.67% in the "very good" category, the media expert validation data showed an average of 96.83%, and the teacher's response results showed an average of 86.64% with the "very good". Trials were also conducted on students by obtaining an average presentation on each component aspect, namely according to the criteria, language, graphics and usability with an average proportion of e-modules of 82.03% with the criteria of "very good". The results of understanding the concept of students were carried out pretest posttest control group design with experimental and control classes. The results of the increase are quite effective with an average N-Gain of 62.9%. In addition, the acquisition of students who completed the Minimum Passing Criteria was 100 percent, while only 83.33% had completed the Minimum Passing Criteria in the control class. On the whole it can be guaranteed that the E-module is very feasible and effective enough to be applied in learning